Development of the Cultural Tightness-Looseness Orientation Scale for College Students - Sun S; Zhang H (Psychology Research and Behavior Management, 2023)
Shuwei Sun,1 Haiyan Zhang2 1School of Mathematics and Statistics, Xuzhou University of Technology, Xuzhou, Jiangsu, People’s Republic of China; 2Business School, Jiangsu Normal University, Xuzhou, Jiangsu, People’s Republic of ChinaCorrespondence: Haiyan Zhang, Business School, Jiangsu Normal University, No. 101 Shanghai Road, Tongshan, Xuzhou, Jiangsu, 221116, People’s Republic of China, Tel +86 15996963625, Email zhy3625@jsnu.edu.cnBackground: “The cultural tightness-looseness orientation of college students”, which involves college students’ cognition about tolerance for non-learning-behavior in class, strength of learning-behavior norms in class, and strength of social norms in the generalized macro-context, offers a new perspective to explain college students’ psychology and behavior and could effectively promote their all-round development. However, there is severely lack of a reliable and valid instrument. Hence, we seek to develop the Cultural Tightness-Looseness Orientation Scale for College Students (CTLOS-S) in the Chinese context.Methods: We firstly pooled the initial 17 measuring items of CTLOS-S through literature review and the open-ended interview. After conducting questionnaire survey among 264 college students using the initial scale, we did a series of reliability and validity tests to get the formal CTLOS-S, based on which we further administered questionnaire survey among 755 college students to check its reliability, construct validity, criterion validity, content validity, and across-gender invariance.Results: The formal CTLOS-S contains 7-item subscale of tolerance orientation for non-learning-behavior in class, 4-item subscale of strength orientation of learning-behavior norms in class, and 3-item subscale of strength orientation of social norms in the generalized macro-context. The testing results of the second-stage questionnaire survey data (N = 755) demonstrate that the reliability coefficients of CTLOS-S and its three subscales are 0.85, 0.85, 0.83, and 0.76 separately, the internal 3-factor structure validity of CTLOS-S is satisfactorily acceptable with χ2(74) = 318.76, CFI = 0.94, TLI = 0.93, RMSEA = 0.06, and SRMR = 0.04, and the content validity and criterion validity are satisfactory as the total score of CTLOS-S is positively correlated with each score of its three subscales and the total score of learning engagement scale. Besides, the 3-factor structure of CTLOS-S is invariant across gender.Conclusion: The 14-item CTLOS-S we develop is a reliable and valid instrument for researchers to conduct quantitative studies on college students’ cultural tightness-looseness orientation.Keywords: the cultural tightness-looseness orientation of college students, tolerance orientation for non-learning-behavior in class, strength orientation of learning-behavior norms in class, strength orientation of social norms in the generalized macro-context